Implementation of a digital behavior change intervention (eCHANGE) for weight loss maintenance support: a service design and technology transfer approach - R. A. Asbjørnsen; R. A. Asbjørnsen; R. A. Asbjørnsen; J. Hjelmesæth; J. Hjelmesæth; M. L. Smedsrød; J. Wentzel; M. M. Clark; S. M. Kelders; J. E. W. C. van Gemert-Pijnen; L. Solberg Nes; L. Solberg Nes; et al. (Frontiers Media S.A., 2024)
Obesity is a chronic disease, and while weight loss is achievable, long-term weight loss maintenance is difficult and relapse common for people living with obesity. Aiming to meet the need for innovative approaches, digital behavior change interventions show promise in supporting health behavior change to maintain weight after initial weight loss. Implementation of such interventions should however be part of the design and development processes from project initiation to facilitate uptake and impact. Based on the development and implementation process of eCHANGE, an evidence-informed application-based self-management intervention for weight loss maintenance, this manuscript provides suggestions and guidance into; (1) How a service design approach can be used from initiation to implementation of digital interventions, and (2) How a technology transfer process can accelerate implementation of research-based innovation from idea to market.